The Effectiveness of Integration Model of Disaster Risk Reduction with the Living Values Education Approach in Thematic Learning in Primary School - Pambudi, Dholina Inang; Suyatno; Fatmawati, Laila (American Journal of Education and Learning, 2020)
Bantul Regency is the area that has a high disaster potential. This regency ranked 22, which was potentially catastrophic districts In Indonesia. Therefore, Disaster Risk Reduction efforts in this area need to be conducted systematically and sustainably by involving all stakeholders. This research aimed to develop the integration model of Disaster Risk Reduction by using a Living Values Education approach in thematic learning in primary school. The developed model has been tested in two elementary schools in Bantul Regency by using the pre-experimental design of one group Pretest-Postest. The population in this study was school principals and teachers from the Aisyiyah top primary schools of Bantul, and Muhammadiyah primary school of Bantul City. Sampling used the purposive sampling approach with the sample selection process that was gained by 20 teachers and two school principals as research samples. The data collection technique was through a questionnaire sheet using Likert’s Scale guidelines scales from 1 to 5. Data analysis techniques used non-parametric tests with the Wilcoxon Signed Rank Test technique because the data used was not a normal distribution. The results of the test showed the value of Sig. 0.000 < 0.05, furthermore, it can be concluded that the integration model of Disaster Risk Reduction by the Living Values Education approach was effective in developing the knowledge, attitudes, and skills of the principal and teachers. These research findings could be considered for policy stakeholders to plan and develop teacher competencies in integrating Disaster Risk Reduction programs in primary school learning.